Створення ізометричних ілюстрацій та їх використання в графічному дизайні - Петрова, К. (My University, 2020)
Isometric illustrations are widely used in web design. Creating them is a difficult task. The purpose of the work is to develop modern software to automate the process of creating isometric illustrations
Keywords: ізометричні ілюстрації; графічний дизайн